Penyusunan Peta Potensi Desa Tanjung Seru Sebagai Media Informasi dan Perencanaan Pembangunan Desa - Salsa Dwi Oktalia; Trisna Trisna; Ovetri Viorenika (CV. ITTC INDONESIA, 2026)
This study aims to develop a potential map of Tanjung Seru Village as an information medium and a basis for village development planning. The study focuses on identifying the village's natural resources, human resources, infrastructure, and economic potential. A qualitative approach with a descriptive method was employed. Data were collected through field observations, interviews with village officials and community members, and documentation studies of the village profile. The data analysis consisted of identifying village potentials, processing spatial data using a Geographic Information System (GIS), presenting the potential map, and drawing conclusions. The results indicate that Tanjung Seru Village possesses considerable potential in the agricultural, plantation, natural resource, and infrastructure sectors, which can be further developed to support village development. The resulting potential map provides systematic spatial information that serves as an effective information medium for both the local community and village government in determining development priorities. In conclusion, the preparation of a village potential map can support a more targeted, effective, and locally based village development planning process.